2016
DOI: 10.12688/f1000research.10031.1
|View full text |Cite
|
Sign up to set email alerts
|

New discoveries in the molecular landscape of bladder cancer

Abstract: We are currently on the cusp of exponential growth in the understanding of the molecular landscape of bladder cancer. Emerging data regarding the mutational burden and targetable genomic and protein alterations in bladder cancer have allowed us to tap into treatments directed toward specific molecular characteristics of bladder cancer. In parallel, these developments will enable us to better select patients for existing treatments of bladder cancer in a step toward personalized therapy. The present article rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Several metabolic altered pathways are involved in bladder tumorigenesis 27 . With the advancement of multi-omics analysis, de novo identification of oncogenes have been carried out in various types of cancers, including BLCA 28 . A most recent multi-omics study has shown that fatty acid metabolism plays a central role in facilitating the progress of BLCA 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Several metabolic altered pathways are involved in bladder tumorigenesis 27 . With the advancement of multi-omics analysis, de novo identification of oncogenes have been carried out in various types of cancers, including BLCA 28 . A most recent multi-omics study has shown that fatty acid metabolism plays a central role in facilitating the progress of BLCA 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Omics studies have identified therapeutic targets and resulted in the successful development of new drugs to treat various solid tumors like breast cancer and lung cancer (4,5). For bladder cancer, prognostication and treatment still depend mainly on pathologic and clinical characteristics (6). Patients diagnosed with high-grade invasive disease are difficult to treat effectively and have a relatively low life expectancy despite available multimodal therapies.…”
Section: Introductionmentioning
confidence: 99%